PENGEMBANGAN VIDEO ETNOSAINS PADA MATERI SISTEM RANGKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA - Lubis, Silvi Puspa Widya; Maslida, Maslida; Hamama, Syarifah Farissi; Samsuar, Samsuar (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to develop an ethnoscience-based educational video about the human skeletal system for 11th- grade students at SMA Negeri 1 Indrapuri, Aceh Besar. The research employs a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate) by Thiagarajan. The video, developed using the CapCut application, integrates the traditional Acehnese dance, Ranup Lampuan, with the concept of the human skeletal system. Validation conducted by three media experts showed a validity percentage of 79.41%, which is categorized as feasible. The ethnoscience-based video, using the Ranup Lampuan dance to teach the skeletal system, is designed to incorporate local wisdom into biology education. The Ranup Lampuan dance, a part of Acehnese culture, was chosen because its graceful and structured movements represent various functions of bones and joints in the human body, helping students understand the material in a more contextual and meaningful way. This educational video not only serves as a learning medium but also as a tool for preserving local culture and instilling cultural pride in students.